An Autism-Related, Nonsense Foxp1 Mutant Induces Autophagy and Delays Radial Migration of the Cortical Neurons. (15th August 2018) - Li, Xue; Han, Xin; Tu, Xiaomeng; Zhu, Dan; Feng, Yue; Jiang, Tian; Yang, Youping; Qu, Jia; Chen, Jie-Guang
Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder that has a strong genetic component. Disruptions of FOXP1, a transcription factor expressed in the developing cerebral cortex, were associated with ASD. FOXP1(R525X) is a de novo heterozygous mutation found in patients with autism and severe mental retardation. To explore the neuronal basis of FOXP1(R525X) in ASD, we created Foxp1(R521X), a mouse homolog of the human variant. Ectopic expression of Foxp1(R521X) led to cytoplasmic aggregates and activated macroautophagy in neuroblastoma N2a cells and the developing neuronal cells. Cortical neurons expressing Foxp1(R521X) exhibited delayed migration and altered dendritic morphology. As a control, mutant Y435X that was expressed diffusively in the cytoplasm did not induce autophagy and migration delay in the cortex. The embryonic cortical cells had a minimal activity of nonsense-mediated mRNA decay (NMD) as assayed by a splicing-dependent NMD reporter. We hypothesize that the developing neuronal cells use autophagy but not NMD as a safeguard mechanism against nonsense mutant aggregates, resulting in impairment of the cortical development. This study suggests a novel mechanism other than heterozygous loss of FOXP1 for the development of ASD and may advance our understanding of the complex relationships between gene mutation and the related psychiatric disorders.